A reconsideration of the Jensen-Meckling model of outside finance - Martin Hellwig (Max Planck Institute for Research on Collective Goods, 2007)
The paper studies outside finance in a model of two-dimensional moral hazard, involving risk choices as well as effort choices. If the entrepreneur has insu cient funds, a first-best outcome cannot be implemented. Second-best outcomes involve greater failure risk than first-best outcomes. For a Cobb-Douglas technology, second-best effort and investment levels are smaller than first-best; for other technologies, they depend on the elasticity of substitution. If firm returns not too noisy signals of be-haviour, suitable incentives can be provided by some mix of debt and equity issues. If firm returns involve too much noise, this is not possible.
Keywords: D86; G30; G32; 330; Financial Contracting; Debt Finance; Equity Finance; Moral Hazard; Risk Choices; Unternehmensfinanzierung; Agency Theory; Moral Hazard; Theorie